Pengaruh Stres Kerja, Kompensasi dan Kepuasan Kerja Terhadap Turnover Intention Studi Pada Karyawan kontrak PT. Gagah Satria Manunggal Banjarmasin - Muhammad Khaidir; Ahmad Alim Bachri; Tinik Sugiati (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This study aims to analyze the influence of job stress (X1), compensation (X2) and job satisfaction (X3) as independent variables either partially or simultaneously toward turnover intention (Y) as the dependent variable on contract employees of PT. Gagah Satria Manunggal Banjarmasin. The method of this research used a questionnaire with 45 contract employees of PT. GSM Banjarmasin as the samples and they were selected from population of 54 employees. The variables were measured using Likert scale technique with a weight scale from 1 to 5. To analyze the variables X1, X2, X3 to Y, statistical technique of multiple linear regression analysis was used, and to test the significance rate, F test was used, and t test was processed with the SPSS software application program. The results of the research concluded that there was a positive significant influence from each independent variable toward the dependent variable. From the three independent variables, job stress had a dominant influence compared with two other independent variables. And there was a significant simultaneously influence from the three independent variables towards the employee’s turnover intention.